2016
DOI: 10.4142/jvs.2016.17.2.127
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aluminum on the reduction of neural stem cells, proliferating cells, and differentiating neuroblasts in the dentate gyrus of D-galactose-treated mice via increasing oxidative stress

Abstract: Aluminum (Al) accumulation increases with aging, and long-term exposure to Al is regarded as a risk factor for Alzheimer's disease. In this study, we investigated the effects of Al and/or D-galactose on neural stem cells, proliferating cells, differentiating neuroblasts, and mature neurons in the hippocampal dentate gyrus. AlCl3 (40 mg/kg/day) was intraperitoneally administered to C57BL/6J mice for 4 weeks. In addition, vehicle (physiological saline) or D-galactose (100 mg/kg) was subcutaneously injected to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…As a-synuclein level was significantly high in the cerebrospinal fluids in patients with AD, a-synuclein was considered an early pathophysiological event in the development of AD. 42,43 In the present study, sildenafil increased VEGF-A content and decreased immunoexpression of a-synuclein in brain areas. Increased VEGF-A is linked to neovascularization and increased tissue perfusion.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…As a-synuclein level was significantly high in the cerebrospinal fluids in patients with AD, a-synuclein was considered an early pathophysiological event in the development of AD. 42,43 In the present study, sildenafil increased VEGF-A content and decreased immunoexpression of a-synuclein in brain areas. Increased VEGF-A is linked to neovascularization and increased tissue perfusion.…”
Section: Discussionsupporting
confidence: 58%
“…As α-synuclein level was significantly high in the cerebrospinal fluids in patients with AD, α-synuclein was considered an early pathophysiological event in the development of AD. 42,43…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, it was shown that Al accelerates the reduction of neural stem cells, proliferating cells and differentiating neuroblasts (Nam et al . ). Previous experiments have also shown that aluminium accumulates both in neurons and astrocytes, causing in the latter major changes in the morphology including shrinkage of cell bodies and retraction of processes, also reducing astrocyte viability (Suárez‐Fernández et al .…”
Section: Discussionmentioning
confidence: 97%
“…Explicitly, the PL intensity of CDs exhibits good linearity in a broad concentration range of ions (linear detection region) and a low detection limit, meaning that ion concentrations of the order of 10 −7 and lower can be detected. Undoubtedly, one of the most interesting metal ions is Al 3+ because it is related to ageing [51], reduction of neural stem cells [51], high-risk factor for kidney damage [50,51], Alzheimer's [49,50] and Parkinson's diseases [49,50].…”
Section: Metal Ion Sensingmentioning
confidence: 99%